O Conselho Municipal de Educação de Uberlândia (2015-2019): participação na democratização do ensino municipal - Santos, Elyane Thayara Souza (2020)
This dissertation, located in the Work, Society and Education line of research, aims to analyze: the performance of the Municipal Education Council of the Uberlândia - CMEU in the Municipal Education network, from 2015 to 2019; its possible contribution to the process of democratization of education, examining the aspects that influence and interfere in this process; the existence of participation in the elaboration, construction and inspection of public policies within the scope of municipal public education; the possibility of implementing the Municipal Education System; the determining factors that favour, hinder and/or impede the effective participation of the Municipal Education Council in the democratic management of municipal public education. The thesis sought to answer the following questions: How does decision-making occur? Is this process inclusive (do all individuals participate?). When decisions are made, how are these decisions socialized? Do the decisions express concern for community welfare, for municipal education? Which interests do they meet? In order to achieve the proposed objectives, a theoretical study was carried out through bibliographic research of document analysis. In the bibliographic research, the main authors who discuss participation and education councils were considered. The documentary research was based on the records of the Municipal Education Council of the Uberlândia Minutes, the laws that deal with the council and educational legislation.